Numerical simulation and experimental study on hydraulic characteristics of L-shaped baffle fishway - Liu, Yongsheng; Tang, Jianping; Liu, Benqin; Wang, Neng; Ye, Yasi; Miao, Jiankang (Frontiers in Mechanical Engineering, 2025)
The rapid expansion of hydraulic infrastructure has profoundly disrupted fish migration pathways in riverine ecosystems. To address this challenge, this study investigated the fishway at China’s Zhuzhou Hub, comparing conventional L-type and H-type baffle designs. A mathematical framework based on the k-ε turbulence model was employed to characterize the hydraulic behavior of these structures, with numerical solutions derived via the finite volume method. A comprehensive 1:6 scale physical model was then used to validate hydraulic performance, analyzing flow field structure in pool chambers, velocity distribution at vertical slots, and water surface profile variations under varying water levels. Results demonstrate that the L-type baffle configuration yields slot velocities of 0.28–0.87 m/s (mean: 0.50–0.77 m/s), meeting the critical swimming requirements of the “Four Major Chinese Carps” (black carp, grass carp, silver carp, and bighead carp) (response velocity: 0.2 m/s; critical velocity: 1.3 m/s). The main flow exhibited a smooth S-shaped curvature with lower flow distortion than the H-type baffle, while low-velocity zones (<0.3 m/s) occupied over 50% of the chamber area, ensuring both fish passage efficiency and resting opportunities. Experimental observations showed strong agreement with simulation data, confirming the accuracy of the mathematical framework and numerical methodology. These findings provide robust theoretical and practical guidance for optimizing fishway designs to enhance migratory success and ecological sustainability in regulated rivers.